The Significanity of Academic Manuscripts Dignity on Legal Products - Muhammad Ramadhana Alfaris; Sulthon Miladiyanto (Universitas Widya Gama Malang, 2023)
Various norms in laws in Indonesian regional legislatures are not always colored by academic nuances that are substantially objective to draft regulations, more tend to be political interests. So that the results obtained on the legal product are of low quality because the legal product does not have an academic background. The purpose of this study was to determine the significanity of the dignity of academic manuscript on the formation of Regional Regulations. The method used in this study uses a normative juridical method with a conceptual approach, legislation and legal research on the level of vertical and horizontal synchronization to examine the problems in this research. The results of the study indicate that academic manuscript have significanity for the situation that is needed for the movement of the wheels of state government, especially in the regions. Because academic manuscript in the aspect of having a very high position in the formation of laws and regulations, the significanity of which is to measure the good or bad of legal products.